Hungary : Request for Stand-By Arrangement-Staff Report; Staff Supplement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
This staff report for the Request for Stand-By Arrangement of Hungary examines financing conditions and economic challenges. Hungary was among the first emerging market countries to suffer from the fallout of the current global financial crisis. Compared with other emerging markets, Hungary's higher stock vulnerabilities imply that a large amount of debt needs to be serviced and rolled over. Added risks include the large share of foreign currency lending by both domestic banks and subsidiaries of foreign parents.